2019
DOI: 10.7717/peerj.5828
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and nitrogen isotopic composition of commercial dog food in Brazil

Abstract: Background Brazil is a low- to medium-income country and has the second largest pet food market in the world with 8% of world pet food consumption. The lowest-income social class spends around 17% of their domestic budget on pet food and other items related to pets. Consumers are frequently misled by advertising as there is no precise information about the main sources of protein, carbohydrates and fat in the labels, and the Brazilian pet food industry can legally claim that their products contain certain item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…In an animal that eats only one or a select few food sources, such as a grazing Merino sheep, the δ 13 C value range is 0.84 (Männel, Auerswald & Schnyder, 2007). The ranges in food isotope values we obtained are very similar to those obtained in a recent Brazilian study looking at the contents of food for domestic dogs (Galera et al, 2019). The cats in our study, from both the US and UK, had δ 13 C value ranges of around 6 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In an animal that eats only one or a select few food sources, such as a grazing Merino sheep, the δ 13 C value range is 0.84 (Männel, Auerswald & Schnyder, 2007). The ranges in food isotope values we obtained are very similar to those obtained in a recent Brazilian study looking at the contents of food for domestic dogs (Galera et al, 2019). The cats in our study, from both the US and UK, had δ 13 C value ranges of around 6 .…”
Section: Discussionsupporting
confidence: 83%
“…Because most pet cats are consistently fed one kind of food at home, and because many pet foods are thought to include corn or corn-fed livestock (Schnepf, 2011;Galera et al, 2019), we expected that a stable isotope approach would have a high power to discern pets consuming native prey from those eating only pet food. However, we found that the high variability of isotope values for pet foods, across and within brands, not to mention across countries, makes it extremely difficult to determine the diet of individual cats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation